The deployment of ICT facilities in teaching and learning in Higher Education: a mixed method study of its impact on lecturers and students = A implantação de instalações de tic no ensino e aprendizagem no ensino superior: um estudo de método misto de seu impacto sobre professores e alunos - Adedokun-Shittu, Nafisat Afolake; Sheikh Ahmad, Ismail; Othman, Joharry; Tunku Ahmad, Tunku Badariah (Universidade Municipal De Sao Caetano Do Sul, 2012)
This study employed mixed method consisting qualitative and quantitative procedures to exa- mine the impact of ICT in teaching and learning at a University in Nigeria. The survey data were drawn from 593 respondents (students and lecturers) and was analyzed using linear regression. For the qualitative part, one-on-one and focus group interviews were conducted among 7 students and 8 lecturers to seek their varying opinion on ICT impact on teaching and learning. Lecture-room observations were conducted across 3classes to see how ICT is integrated. These multiple means findings were triangulated, compared and contrasted to validate the study. Predictors of ICT impact were found to be perception, integration, motivation and challenges. The qualitative interview and observation findings generated 4 similar themes as the quantitative result which was conceptualized as a model that serves as a framework for researchers on impact assessment.